Pendidikan Agama Hindu Sebagai Sarana Pembentukan Karakter dan Kesadaran Ekologis Generasi Muda - Widasni, Nyoman; Wiliantari, Ni Ketut Ari; Paramitha, Nia Ayu; Ningsih, Kadek Ayu; Asih, Dewa Ayu Rastiti (Pratyaksa: Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
The purpose of this study is to examine the teachings that play a role in shaping character and environmental awareness within Hindu religious education. This research employs a qualitative method with a case study approach. The findings reveal that Hindu religious education provides a strong foundation for individuals to understand and internalize spiritual values deeply. This includes an understanding of philosophical concepts such as karma (the law of cause and effect), dharma (moral duty), and moksha (spiritual liberation), as well as other teachings that guide humans toward the path of perfection. In addition, Hindu education emphasizes spiritual practices such as worship, meditation, and maintaining balance between body, mind, and soul. These practices help cultivate positive traits such as patience, wisdom, and inner peace, which are essential components of character development. Hindu religious education also plays a significant role in instilling a sense of love and respect for nature from an early age. The teachings found in Hindu scriptures provide profound insights into the interconnectedness between humans and the universe. Therefore, Hindu religious education serves as an important pillar in nurturing a young generation that is moral, ethical, and environmentally conscious. However, to ensure that Hindu education remains relevant and effective in addressing contemporary challenges, comprehensive efforts toward improvement and renewal are needed to maximize its positive impact on society.